Social and spatial conflict drive resident aggression toward outsiders in a group-living fish. (25th May 2021) - Gübel, Jakob; Bose, Aneesh P H; Jordan, Alex
Abstract: Group-living animals often experience within-group competition for resources like shelter and space, as well as for social status. Because of this conflict, residents may aggressively resist joining attempts by new members. Here, we asked whether different forms of competition mediate this response, specifically competition over 1) shelter, 2) spatial position within groups, and 3) social or sexual roles. We performed experiments on wild groups of Neolamprologus multifasciatus cichlids in Lake Tanganyika, either increasing or decreasing the number of shelters (empty snail shells) within their territories. We predicted that increases in resource abundance would reduce conflict and lower the aggression of residents toward presented conspecifics, while decreases in resources would increase aggression. We explored the effects of social conflict and spatial arrangement by introducing same or opposite sex conspecifics, at greater or lesser distances from resident subterritories. We found that changing the abundance of shells had no detectable effect on the responses of residents to presented conspecifics. Rather, aggression was strongly sex-dependent, with male residents almost exclusively aggressing presented males, and female residents almost exclusively aggressing presented females. For females, this aggression was influenced by the spatial distances between the presented conspecific and the resident female subterritory, with aggression scaling with proximity. In contrast, presentation distance did not influence resident males, which were aggressive to all presented males regardless of location. Overall, our results show that group residents respond to presented conspecifics differently depending on the type of competitive threat these potential joiners pose. Abstract : Group living is associated with numerous challenges, including how to share limited space and resources among group members, and how to divide social roles. These challenges generate conflict among group members and outsiders. We find that changing within-group resource abundance does not affect responses, but that aggression is highest when residents and outsiders are of the same sex, and for females, when the outsider is in close proximity to her subterritory.